Postmating Reproductive isolation between strains of Drosophila willistoni - Mardiros, Xian B. (Fly (Austin), 2016)
Speciation can occur through the presence of reproductive isolation barriers that impede mating, restrict cross-fertilization, or render inviable/sterile hybrid progeny. The D. willistoni subgroup is ideally suited for studies of speciation, with examples of both allopatry and sympatry, a range of isolation barriers, and the availability of one species complete genome sequence to facilitate genetic studies of divergence. D. w. willistoni has the largest geographic distribution among members of the Drosophila willistoni subgroup, spanning from Argentina to the southern United States, including the Caribbean islands. A subspecies of D. w. willistoni, D. w. quechua, is geographically separated by the Andes mountain range and has evolved unidirectional sterility, in that only male offspring of D. w. quechua females × D. w. willistoni males are sterile. Whether D. w. willistoni flies residing east of the Andes belong to one or more D. willistoni subspecies remains unresolved. Here we perform fecundity assays and show that F1 hybrid males produced from crosses between different strains found in Central America, North America, and northern Caribbean islands are reproductively isolated from South American and southern Caribbean island strains as a result of unidirectional hybrid male sterility. Our results show the existence of a reproductive isolation barrier between the northern and southern strains and suggest a subdivision of the previously identified D. willistoni willistoni species into 2 new subspecies.